Sustainable development and profitability as contribution factors towards the survival of organizations: an approach based on the analysis of Natura Cosméticos S.A.s annual report - Lenza, Elisabeth Rayle Bortucan; Lapini, Paulo Alencar; Camargo, Silvia Helena Ramos Valladão de (Revista Gestão da Produção Operações e Sistemas, 2008)
Environmental problems have become topics of discussion in scientific, academic and popular fields, pressuring those who could be considered most responsible: the government, in political and economical aspects, but also the business community. Therefore, this article aims at demonstrating it is possible to reconcile economic development with sustainable development, by implementing environmental administration accounting, contributing towards greater control of the reduction in renewable resource expenses and pollutant emission. For such, a bibliographical revision was necessary, and then a research survey to examine the reduction in environmental impacts in 2004, 2005 and 2006, of Natura Cosmeticos Ltd. annual report for 2006. As a result it appears it is possible to ally sustainability with profitability, but this will require company commitment to invest in sustainability which will contribute to the strengthening and greater competitiveness of the company.